The deep learning with Keras workshop : learn how to define and train neural network models with just a few lines of code /: learn how to define and train neural network models with just a few lines of code. (2020) - Moocarme, Matthew; Abdolahnejad, Mahla; Bhagwat, Ritesh
No abstract available